Enhancing Border Gateway Protocol Security Using Public Blockchain - Lukas Mastilak; Marek Galinski; Pavol Helebrandt; Ivan Kotuliak; Michal Ries (Sensors, 2020)
Communication on the Internet consisting of a massive number of Autonomous Systems (AS) depends on routing based on Border Gateway Protocol (BGP). Routers generally trust the veracity of information in BGP updates from their neighbors, as with many other routing protocols. However, this trust leaves the whole system vulnerable to multiple attacks, such as BGP hijacking. Several solutions have been proposed to increase the security of BGP routing protocol, most based on centralized Public Key Infrastructure, but their adoption has been relatively slow. Additionally, these solutions are open to attack on this centralized system. Decentralized alternatives utilizing blockchain to validate BGP updates have recently been proposed. The distributed nature of blockchain and its trustless environment increase the overall system security and conform to the distributed character of the BGP. All of the techniques based on blockchain concentrate on inspecting incoming BGP updates only. In this paper, we improve on these by modifying an existing architecture for the management of network devices. The original architecture adopted a private blockchain implementation of HyperLedger. On the other hand, we use the public blockchain Ethereum, more specifically the Ropsten testing environment. Our solution provides a module design for the management of AS border routers. It enables verification of the prefixes even before any router sends BGP updates announcing them. Thus, we eliminate fraudulent BGP origin announcements from the AS deploying our solution. Furthermore, blockchain provides storage options for configurations of edge routers and keeps the irrefutable history of all changes. We can analyze router settings history to detect whether the router advertised incorrect information, when and for how long.